Power generating element and method for manufacturing the same

The power generation element addresses inefficiencies and environmental concerns by using a laminated structure of silicon dioxide and metal layers with moisture-retaining properties, enhancing power generation efficiency and sustainability.

JP7602221B1Active Publication Date: 2024-12-18INFINITE ENERGY TECHNOLOGIES CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024074569
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-01
Publication Date
2024-12-18
Estimated Expiration
2044-05-01

AI Technical Summary

Technical Problem

Existing power storage devices face challenges such as high internal resistance, poor durability, self-discharge, and environmental impact due to the use of toxic materials, making them inefficient and unsustainable.

Method used

A power generation element is developed using a laminated structure of silicon dioxide and metal layers, with specific ionization tendencies, and moisture-retaining layers to enhance power generation efficiency without requiring external charging, utilizing materials like tuff and silicon dioxide for increased ion absorption.

Benefits of technology

The solution achieves efficient power generation with reduced environmental impact, being small and lightweight, and stable over time, without the need for external voltage charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602221000001_ABST
    Figure 0007602221000001_ABST
Patent Text Reader

Abstract

An object of the present invention is to provide a power generating element that does not require charging with an external voltage, is small and lightweight, and yet has high power generating efficiency, and a method for manufacturing the power generating element. [Solution] The power generating element 1 comprises a substrate layer 10 containing moisture, a first electrostatic layer 20 containing silicon dioxide and a first metal layer 40 containing a predetermined type of metal laminated in this order in the stacking direction on one surface of the substrate layer 10, and a second electrostatic layer 30 containing silicon dioxide and a second metal layer 50 containing a predetermined type of metal with a smaller ionization tendency than the metal contained in the first metal layer 40 laminated in this order in the stacking direction on the other surface of the substrate layer 10. Negative ions released from the first metal layer 40 are taken in by the first electrostatic layer 20 and the second electrostatic layer 30, and current can be extracted as electrons move from the first metal layer 40 to the second metal layer 50.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a power generating element and a method for manufacturing the power generating element. More specifically, the present invention relates to a power generating element that does not require charging with an external voltage, is small and lightweight, and yet can improve power generation efficiency, and a method for manufacturing the power generating element. [Background technology]

[0002] In recent years, the demand for electrical devices, such as mobile phones, smartphones, and notebook personal computers, has been increasing rapidly, and this is one of the fields expected to grow further in the future. As such electrical devices become more widespread, research and development of power storage devices, which are the driving sources of such devices, is also being actively carried out. In addition, due to the growing interest in global environmental issues and petroleum resource issues, next-generation clean energy vehicles such as hybrid electric vehicles (HEVs), electric vehicles (EVs), and plug-in hybrid electric vehicles (PHEVs) are attracting attention, and the importance of power storage devices in various applications will continue to increase in the future.

[0003] Generally, lead-acid batteries and nickel-cadmium batteries have been used as power storage devices, but regulations on batteries containing such harmful heavy metals are gradually becoming stricter due to the demands of an environmentally conscious society. In addition, with the spread of small portable information terminals, there is an increasing demand for higher energy density, higher voltage, higher output, longer life, smaller size and weight, lower cost, etc., and as a result, lithium-ion batteries, electric double layer capacitors, lithium-ion capacitors, etc. have been developed and are becoming more widespread as new power storage devices.

[0004] A lithium-ion battery generally comprises a positive electrode in which a positive electrode active material and the like are applied to both sides of a positive electrode current collector using a binder, and a negative electrode in which a negative electrode active material and the like are applied to both sides of a negative electrode current collector using a binder, the positive electrode and the negative electrode being connected via an electrolyte layer and housed in a battery exterior material. For example, Patent Document 1 describes a lithium-ion battery with a stacked structure in which 19 positive electrodes and 20 negative electrodes are alternately stacked with electrolyte layers between them.

[0005] Patent Document 2 discloses a power supply device that charges a secondary battery with electricity generated by a power generating element and uses it as auxiliary energy. Specifically, electricity generated by a piezoelectric element is charged into a secondary battery or a capacitor, and this electrical energy is used as auxiliary energy for the power supply battery of a portable terminal device, thereby realizing long-term use of the portable terminal device.

[0006] However, because the operating principle of lithium-ion batteries is based on chemical reactions (Faraday reactions), they have excellent energy density, but they also have the disadvantages of high internal resistance and poor durability. Therefore, in devices that use lithium-ion batteries, losses due to internal resistance are large, making it difficult to efficiently charge the minute amounts of power generated by the power generation element. In addition, because they have low durability against repeated charging and discharging and in high-temperature environments, maintenance such as replacement at regular intervals is required.

[0007] In addition, since the operating principle of a capacitor is not a chemical reaction but storing electric charge by electrostatic adsorption of ions in an electrolyte, the capacitor has excellent internal resistance and durability, but the accumulated electric charge disappears quickly because the adsorbed ions diffuse and self-discharge occurs quickly. Therefore, if the power generation by the power generation element is intermittent and the power generation interval is long, the discharge from the storage device may not function properly.

[0008] Furthermore, although the above-mentioned lithium ion batteries and capacitors have different service lives depending on the application and method of use, they will inevitably reach the end of their lifespan, and for example, lithium ion batteries installed in hybrid cars and electric cars will eventually be discarded as used batteries. When disposing of these used lithium ion batteries, valuable metals contained in each component are recovered and recycled as resources, but the reality is that most of them are discarded as industrial waste, which places a large burden on the environment. For this reason, in recent years, there has been a demand for the development of an electricity storage device that places a low burden on the environment.

[0009] In this regard, Patent Document 3 discloses a power generating element that is manufactured from volcanic ash that has a large amount of static electricity and does not require disposal. Specifically, a static electricity generating member made of fine hollow spheres processed from volcanic ash, other minerals, and activated mineral water containing negative ions is filled into an insulating, airtight cylindrical container with conductive water-containing powder made of activated carbon, fullerene, nanotubes, etc., and then an anode electrode and a cathode electrode for extracting electricity are connected to both ends of the container, thereby realizing the extraction of a large amount of electricity despite its small size.

[0010] Furthermore, as shown in Patent Document 4, the inventors of the present application have discovered that shirasu balloons, which are made by baking shirasu, a volcanic ejecta, at high temperatures of approximately 1000°C to foam and expand it, have the property of absorbing a large amount of negative ions. Based on this knowledge, they have developed a power generation element consisting of a laminated structure in which a shirasu balloon is sandwiched between metals with different ionization tendencies, and have realized a technology that can stably extract current for long periods of time. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2009-272048 A [Patent Document 2] JP 2002-171341 A [Patent Document 3] Special Publication No. 2005-502180 [Patent Document 4] Patent No. 6547082 Summary of the Invention [Problem to be solved by the invention]

[0012] According to the inventions disclosed in Patent Documents 3 and 4 above, the power generating element is made of volcanic ash and shirasu as its main materials, and therefore does not require special disposal, resulting in a low environmental impact and a pollution-free, clean power generating element.

[0013] However, in the invention of Patent Document 3, attention is focused on the ion exchange properties of allophane contained in volcanic ash, and the volcanic ash is impregnated with an aqueous solution of negative ions to form a static electricity generating member, and the static electricity generated in the static electricity generating member is extracted as electromotive force. Therefore, whenever the amount of accumulated static electricity becomes low, it is necessary to add an aqueous solution of negative ions.

[0014] Furthermore, when generating a negative ion aqueous solution, for example when using tap water, it is necessary to reduce the molecular clusters contained in the tap water and convert them into negative ions; however, this generally requires the use of special substances such as ceramic chips or tourmaline, and the manufacturing process is also complicated, making it difficult to secure a sufficient amount of negative ion aqueous solution.

[0015] Furthermore, according to the inventor's research, it is known that volcanic ash contains elements such as silicon and aluminum, gas components such as halogen elements such as fluorine and chlorine, and sulfur, as well as trace metal elements such as copper, zinc, cadmium, and mercury. However, although the presence of these impurities can temporarily generate a large electromotive force, the effect is short-lived, necessitating the frequent addition of an aqueous solution of negative ions.

[0016] In this regard, the invention of Patent Document 4 requires a certain amount of moisture to capture the negative ions into the balloon holes formed in the shirasu balloon layer, but the aqueous solution used does not need to be specially processed and any type of moisture, including tap water, can be used, making it more versatile and enabling a stable current to be extracted for a long period of time.

[0017] On the other hand, the inventors of the present application conducted research into materials with even higher power generation efficiency and discovered that a power generation element with even higher power generation efficiency can be realized by using silicon dioxide (SiO2) as a material to replace the shirasu balloons disclosed in Patent Document 4.

[0018] The present invention has been devised in consideration of the above points, and aims to provide a power generation element that does not require charging from an external voltage, is small and lightweight, and yet can improve power generation efficiency, as well as a method for manufacturing the power generation element. [Means for solving the problem]

[0019] In order to achieve the above-mentioned object, the power generating element of the present invention comprises a substrate layer containing moisture, a first electrostatic layer containing silicon dioxide and a first metal layer containing a predetermined type of metal laminated in this order in a stacking direction on one surface of the substrate layer, and a second electrostatic layer containing silicon dioxide and a second metal layer containing a predetermined type of metal having a smaller ionization tendency than the metal contained in the first metal layer laminated in this order in a stacking direction on the other surface of the substrate layer.

[0020] Here, by providing a base layer, a vapor deposition material can be attached to the base layer to form a power generating element made of a thin film. Since the base layer contains moisture, electrons can be efficiently transferred from the first metal layer to the second metal layer described below, thereby improving power generation efficiency.

[0021] In addition, a first electrostatic layer containing silicon dioxide and a first metal layer containing a predetermined type of metal are stacked in this order in the stacking direction on one side of the base material layer.For example, by using a metal with a relatively high ionization tendency as the first metal layer, it is possible to charge a large number of negative ions to the first electrostatic layer while leaving electrons in the first metal layer.

[0022] In this case, since the first electrostatic layer contains silicon dioxide, which forms a spherical surface, the surface area is large, and a large amount of negative ions can be charged to this surface, thereby improving the power generation efficiency.

[0023] In addition, a second electrostatic layer containing silicon dioxide and a second metal layer containing a predetermined type of metal with a smaller ionization tendency than the metal contained in the first metal layer are stacked in this order in the stacking direction on the other surface of the base material layer, thereby generating an electromotive force. That is, in the first metal layer, electrons are increased by the amount of negative ions absorbed by the first electrostatic layer and the second electrostatic layer. At this time, by conducting the first metal layer and the second metal layer, the electrons generated in the first metal layer move to the second metal layer, and as a result, a current flows between the first metal layer and the second metal layer, generating an electromotive force.

[0024] In addition, when the first and second electrostatic layers are formed by stacking a tuff layer made of tuff or welded tuff and a silicon dioxide layer made of silicon dioxide from the base layer in the stacking direction, the tuff layer can be charged with negative ions in addition to the silicon dioxide layer. Tuff has a large surface area due to the formation of many micropores, and can capture many negative ions into the micropores.

[0025] Furthermore, when the first metal layer is a layer made of at least one metal selected from the group consisting of aluminum, titanium, zinc, chromium, iron, nickel, and lead, by arranging a metal with a relatively high tendency to be ionized as the first metal layer, more negative ions can be absorbed into the charged layer, thereby improving the power generation efficiency.

[0026] Furthermore, when the second metal layer is a layer made of at least one metal selected from the group consisting of gold, silver, copper, and platinum, a greater electromotive force can be generated by stacking a metal having a smaller ionization tendency than the first metal layer as the second metal layer.

[0027] In order to achieve the above object, the power generating element of the present invention comprises an electrostatic layer containing silicon dioxide; The electrostatic charge layer is provided with a first metal layer laminated on one side thereof and containing a predetermined type of metal, a second metal layer laminated on the other side thereof and containing a predetermined type of metal having a smaller ionization tendency than the metal contained in the first metal layer, a first moisture-retaining layer laminated on the first metal layer and containing moisture, and a second moisture-retaining layer laminated on the second metal layer and containing moisture.

[0028] Here, by providing an electrostatically charged layer containing silicon dioxide, silicon dioxide forms a spherical surface, which has a large surface area and can charge a large amount of negative ions on this surface, thereby making it possible to increase the power generation efficiency.

[0029] In addition, by providing a first metal layer containing a predetermined type of metal laminated on one side of the charged layer, and using a metal with a relatively high ionization tendency as the first metal layer, it is possible to charge the charged layer with many negative ions while leaving electrons in the first metal layer.

[0030] Furthermore, by providing a second metal layer, which is laminated on the other surface of the electrostatic layer and contains a specific type of metal with a lower ionization tendency than the metal contained in the first metal layer, the number of electrons in the first metal layer increases by the amount of negative ions absorbed by the electrostatic layer. At this time, by conducting the first metal layer and the second metal layer, the electrons generated in the first metal layer move to the second metal layer, and as a result, a current flows between the first metal layer and the second metal layer, generating an electromotive force.

[0031] In addition, by providing a first moisture-retaining layer that is laminated on the first metal layer and contains moisture, and a second moisture-retaining layer that is laminated on the second metal layer and contains moisture, electrons can be efficiently transferred from the first metal layer to the second metal layer via the first moisture-retaining layer and the second moisture-retaining layer, thereby improving power generation efficiency.

[0032] In addition, when the electrostatic layer contains tuff or welded tuff in a weight ratio of 0.25 to 0.5 for every 1 weight ratio of silicon dioxide, the mixture ratio of silicon dioxide to tuff or welded tuff becomes appropriate, and power generation efficiency can be improved.

[0033] In order to achieve the above-mentioned object, the manufacturing method of the power generation element of the present invention includes the steps of preparing a substrate layer containing moisture, depositing a first electrostatic layer containing silicon dioxide on one surface of the substrate layer, depositing a second electrostatic layer containing silicon dioxide on the other surface of the substrate layer, depositing a first metal layer containing a predetermined type of metal on a surface of the first electrostatic layer opposite to the surface facing the substrate layer, and depositing a second metal layer containing a predetermined type of metal having a smaller ionization tendency than the metal contained in the first metal layer on a surface of the second electrostatic layer opposite to the surface facing the substrate layer.

[0034] Here, by providing a step of preparing a substrate layer containing moisture, a power generating element made of a thin film can be produced by depositing a charging layer (described below) and a substrate layer on both sides of the substrate layer.

[0035] In addition, by providing a step of depositing a first electrostatic layer containing silicon dioxide on one surface of the base layer, and a step of depositing a second electrostatic layer containing silicon dioxide on the other surface of the base layer, electrostatic layers can be laminated on both sides of the base layer. Since this electrostatic layer contains silicon dioxide, a large amount of negative ions can be charged on the spherical surface of the silicon dioxide, which makes it possible to increase the power generation efficiency.

[0036] In addition, the method includes a step of depositing a first metal layer containing a predetermined type of metal on the surface of the first electrostatic layer opposite to the surface facing the base material layer, and a step of depositing a second metal layer containing a predetermined type of metal with a smaller ionization tendency than the metal contained in the first metal layer on the surface of the second electrostatic layer opposite to the surface facing the base material layer, thereby laminating the first metal layer and the second metal layer. Then, in the first metal layer, electrons are increased by the amount of negative ions absorbed by the electrostatic layer. At this time, by conducting the first metal layer and the second metal layer, the electrons generated in the first metal layer move to the second metal layer, and as a result, a current flows between the first metal layer and the second metal layer, generating an electromotive force.

[0037] Furthermore, when the process of depositing the first electrostatic layer and the second electrostatic layer onto the base layer includes a process of depositing a tuff layer made of tuff or welded tuff, and a silicon dioxide layer made of silicon dioxide from the base layer in the stacking direction, each of the tuff layer and the silicon dioxide layer can be charged with negative ions, thereby further improving the power generation efficiency.

[0038] In order to achieve the above-mentioned object, the manufacturing method of the power generating element of the present invention includes the steps of generating an electrostatic layer containing silicon dioxide, laminating a first metal layer on one side of the electrostatic layer, laminating a second metal layer having a lower ionization tendency than the first metal layer on the other side of the electrostatic layer, laminating a first moisture-retaining layer capable of absorbing moisture on either the surface of the first metal layer facing the electrostatic layer or the surface opposite to the surface facing the electrostatic layer, and laminating a second moisture-retaining layer capable of absorbing moisture on either the surface of the second metal layer facing the electrostatic layer or the surface opposite to the surface facing the electrostatic layer.

[0039] Here, by including a step of generating an electrostatically charged layer containing silicon dioxide, the electrostatically charged layer contains silicon dioxide, and therefore a large amount of negative ions can be charged onto the spherical surface of the silicon dioxide, thereby making it possible to increase the power generation efficiency.

[0040] In addition, by including a step of laminating a first metal layer on one side of the electrostatic layer and a step of laminating a second metal layer having a smaller ionization tendency than the first metal layer on the other side of the electrostatic layer, the first metal layer and the second metal layer can be laminated with the electrostatic layer sandwiched between them. Then, in the first metal layer, electrons increase by the amount of negative ions absorbed by the electrostatic layer. At this time, by conducting the first metal layer and the second metal layer, the electrons generated in the first metal layer move to the second metal layer, and as a result, a current flows between the first metal layer and the second metal layer, generating an electromotive force.

[0041] In addition, by laminating a first moisture-absorbing layer on either the surface of the first metal layer facing the charged layer or the surface opposite to the surface facing the charged layer, and providing a second moisture-absorbing layer on either the surface of the second metal layer facing the charged layer or the surface opposite to the surface facing the charged layer, electrons can move efficiently from the first metal layer to the second metal layer via the first moisture-retaining layer and the second moisture-retaining layer, thereby improving power generation efficiency.

[0042] In addition, when the process of generating the electrostatic layer includes a process of mixing tuff or welded tuff in a weight ratio of 0.25 to 0.5 with silicon dioxide in a weight ratio of 1, the mixture ratio of silicon dioxide to tuff or welded tuff becomes appropriate, and the power generation efficiency can be improved. Effect of the Invention

[0043] The power generating element and the method for manufacturing the power generating element according to the present invention do not require charging with an external voltage, and are small and lightweight, yet capable of increasing power generation efficiency. [Brief description of the drawings]

[0044] [Figure 1] 1 is a cross-sectional view that illustrates a schematic diagram of a power generating element according to a first embodiment of the present invention. [Diagram 2] 1A to 1C are diagrams showing application examples using the power generating element according to the first embodiment of the present invention. [Diagram 3] FIG. 4 is a cross-sectional view that shows a schematic diagram of a power generating element according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0045] Hereinafter, embodiments of the present invention will be described with reference to the drawings to facilitate understanding of the present invention.

[0046] [First embodiment] First, the configuration of a power generating element 1 according to a first embodiment of the present invention will be described with reference to Fig. 1. As shown in Fig. 1, the power generating element 1 is in the form of a thin film sheet in which a first electrostatic layer 20 and a first metal layer 40 made of a metal with a high ionization tendency are laminated in the lamination direction on one surface of a base layer 10, and a second electrostatic layer 30 and a second metal layer 50 made of a metal with a low ionization tendency are laminated in the lamination direction on the other surface of the base layer 10.

[0047] The first electrostatically charged layer 20 is made of tuff or welded tuff (hereinafter referred to as "tuff, etc.") and is composed of a first tuff layer 21 having a thickness of 10 nm or more, and a first silicon dioxide layer 22 having a thickness of 10 nm or more and composed mainly of silicon dioxide. The second electrostatically charged layer 30 is made of tuff, etc. and is composed of a second tuff layer 31 having a thickness of 10 nm or more, and a second silicon dioxide layer 32 having a thickness of 10 nm or more and composed mainly of silicon dioxide. In other words, the first electrostatically charged layer 20 and the second electrostatically charged layer 30 each have the same configuration and are composed of a thickness of 20 nm or more.

[0048] In the following description, the first charged layer 20 and the second charged layer 30 may be collectively referred to as the "charged layers", the first silicon dioxide layer 22 and the second silicon dioxide layer 32 may be collectively referred to as the "silicon dioxide layers", and the first tuff layer 21 and the second tuff layer 31 may be collectively referred to as the "tuff layers".

[0049] The first tuff layer 21 and the second tuff layer 31 are formed by foaming tuff or the like by heating it at a high temperature of about 1000 to 1500°C, and forming a thin film on one side and the other side of the base material layer 10. When tuff or the like is foamed by heating it at a high temperature, a large number of bubbles are formed, which increases the overall surface area and makes it possible to charge more negative ions.

[0050] In addition, when forming the power generating element 1 into a thin film, deposition by sputtering is generally performed. In this case, the material to be deposited on the base material layer 10 needs to be a relatively hard material. In this regard, heat-treated tuff, etc., has a certain degree of hardness and is an ideal material for deposition by sputtering.

[0051] The first silicon dioxide layer 22 and the second silicon dioxide layer 32 are composed mainly of silicon dioxide (with a purity of 50% or more). The surface of silicon dioxide is spherical, so it has a large surface area and can be charged with a larger number of negative ions. Like the tuff layer, the silicon dioxide layer is also formed into a thin film by vapor deposition on the tuff layer using sputtering.

[0052] Here, the electrostatically charged layer does not necessarily have to be composed of two layers, a tuff layer and a silicon dioxide layer. As a result of the inventor's investigation, the silicon dioxide layer has a higher ability to charge negative ions than the tuff layer, so the electrostatically charged layer may be composed of only a silicon dioxide layer. When the electrostatically charged layer is composed of only a silicon dioxide layer, silicon dioxide is vapor-deposited on one surface of the base layer 10 to a thickness of 20 nm or more to form a first silicon dioxide layer 22, and silicon dioxide is vapor-deposited on the other surface of the base layer 10 to a thickness of 20 nm or more to form a second silicon dioxide layer 32.

[0053] Furthermore, the electrostatic layer does not necessarily have to have the tuff layer and the silicon dioxide layer laminated in this order in the lamination direction, and may have the silicon dioxide layer and the tuff layer laminated in this order, starting from the base layer 10. However, as described above, when forming a thin film on the base layer 10 by sputtering, it is preferable to deposit a material with as high hardness as possible on the base layer 10. Therefore, as the material to be deposited on the base layer 10, it is preferable to deposit a tuff layer, which is a material with a higher hardness.

[0054] Furthermore, the thickness of each of the first electrostatic layer 20 and the second electrostatic layer 30 is not limited to 20 nm or more. However, as a result of repeated investigations by the inventors, when the total thickness of the electrostatic layer is less than 40 nm, the surface area becomes relatively small and it is not possible to absorb all of the negative ions emitted from the first metal layer 40, so there is a risk that a stable electromotive force cannot be generated.

[0055] On the other hand, it was confirmed that when the total thickness of the electrostatic layer is 40 nm or more, an electromotive force is generated stably, and even if the thickness is changed within a range of, for example, 40 nm or more, there is no significant difference in the generated electromotive force. Therefore, the lower limit of the thickness of each of the first electrostatic layer 20 and the second electrostatic layer 30 is preferably 20 nm, and the upper limit of the thickness of each of the first electrostatic layer 20 and the second electrostatic layer 30 is preferably about 700 nm from the viewpoint of size and weight reduction.

[0056] In the embodiment of the present invention, aluminum is selected as the first metal layer 40 because the ionization energy of the metal is higher than that of hydrogen and is easily immersed in water or acid. The first metal layer 40 is formed by depositing aluminum on the first charged layer 20 by sputtering to form a thin film having a thickness of 20 nm or more.

[0057] Here, the type of the first metal layer 40 does not necessarily have to be aluminum. As described above, any type of metal may be used as long as it has a higher ionization energy than hydrogen and is easily corroded by water or acid, and may be at least one metal selected from, for example, titanium, zinc, chromium, iron, nickel, lead, etc.

[0058] In addition, the first metal layer 40 does not necessarily need to have a thickness of approximately 20 nm, but the inventors' repeated investigations have revealed that a stable electromotive force cannot be generated when the thickness of the first metal layer 40 is less than 20 nm. This is believed to be due to the fact that fewer negative ions are generated in the first metal layer 40 when the first metal layer 40 is in the form of a thin film less than 20 nm.

[0059] On the other hand, it was confirmed that when the thickness of the first metal layer 40 is 20 nm or more, an electromotive force is generated stably, and even if the film thickness of the first metal layer 40 is changed within a range of, for example, 20 nm or more, there is no significant difference in the amount of electromotive force generated. Therefore, the lower limit of the film thickness of the first metal layer 40 is preferably 20 nm, and the upper limit of the film thickness of the first metal layer 40 is preferably about 700 nm from the viewpoint of size and weight reduction.

[0060] In the embodiment of the present invention, copper is selected as the second metal layer 50, which is a metal having a lower ionization energy than hydrogen (i.e., a metal having a lower ionization tendency than the metal material selected for the first metal layer 40). The second metal layer 50 is formed by depositing copper on the second electrostatic layer 30 by sputtering, resulting in a thin film having a thickness of 20 nm or more.

[0061] Here, the type of the second metal layer 50 does not necessarily have to be copper. As described above, any type of metal may be used as long as it has a lower ionization energy than hydrogen, and for example, in addition to copper, it may be at least one metal selected from gold, silver, copper, platinum, etc.

[0062] In addition, the second metal layer 50 does not necessarily need to have a thickness of approximately 20 nm, but the inventors' repeated investigations have revealed that a stable electromotive force cannot be generated when the film thickness of the second metal layer 50 is less than 20 nm. This is believed to be due to the fact that the amount of electrons received from the first metal layer 40 decreases when the second metal layer 50 is made into a thin film having a thickness of less than 20 nm.

[0063] On the other hand, when the thickness of the second metal layer 50 is 20 nm or more, it has been confirmed that an electromotive force is generated stably, and even if the film thickness of the second metal layer 50 is changed within a range of, for example, 20 nm or more, there is no significant difference in the amount of electromotive force generated. Therefore, it is preferable that the lower limit of the film thickness of the second metal layer 50 is 20 nm, and it is preferable that the upper limit of the film thickness of the second metal layer 50 is about 700 nm from the viewpoint of size and weight reduction.

[0064] The base layer 10 is thin, approximately 20 nm thick, and made of a paper material capable of absorbing moisture from the atmosphere, and serves as a base when depositing each layer by sputtering. Since the base layer 10 is made of a material capable of absorbing moisture from the atmosphere, a certain amount of moisture is always contained in the base layer 10. Then, negative ions generated from the first metal layer 40 can be charged to the charging layer via the water molecules absorbed in the base layer 10.

[0065] Here, the thickness of the base layer 10 does not need to be 20 nm, but if the thickness is less than 20 nm, the amount of moisture absorbed by the base layer 10 will be small, which may result in a relative decrease in the number of negative ions that are charged from the first metal layer 40 to the charging layer, resulting in a risk of a decrease in power generation capacity. Therefore, it is preferable to ensure that the thickness of the base layer 10 is 20 nm or more, and from the viewpoint of size and weight reduction, the upper limit of the thickness is preferably about 700 nm.

[0066] Furthermore, as described above, the base layer 10 can absorb moisture from the atmosphere, but a predetermined aqueous solution may be supplied using a dropper, etc. Since it is sufficient that the base layer 10 contains a certain amount of moisture, any type of aqueous solution, including tap water, can be used.

[0067] As described above, by using the base layer 10 as the base material and depositing each layer by sputtering to form a thin film, a power generating element 1 can be obtained that is small and lightweight yet has excellent power generating capacity, and can be used, for example, as a thin battery for mobile devices.

[0068] 2 is a diagram showing an application example using the power generating element 1 according to the first embodiment. By preparing two power generating elements 1a and 1b and connecting the power generating elements 1a and 1b in series via an insulating layer 60, it becomes possible to increase the capacity.

[0069] That is, the second metal layer 50a, which is the positive electrode of the power generating element 1a, and the first metal layer 40b, which is the negative electrode of the power generating element 1b, are connected by a conductor W. Furthermore, a terminal T for taking out electricity is connected to each of the first metal layer 40a, which is the negative electrode of the power generating element 1a, and the second metal layer 50b, which is the positive electrode of the power generating element 1b. This makes it possible to achieve twice the power generating performance compared to a single power generating element 1. Note that, in order to further improve the power generating performance, it is also possible to connect three or more power generating elements in series.

[0070] [Second embodiment] Next, a power generating element 100 according to a second embodiment will be described. Note that descriptions overlapping with those of the first embodiment will be omitted. The power generating element 100 according to the second embodiment is easier to manufacture than the first embodiment in which thin films are formed by deposition using sputtering, since each layer constituting the power generating element 100 is formed by adhesive lamination or the like.

[0071] As shown in FIG. 3, the power generating element 100 according to the second embodiment is composed of an electrostatic layer 110, a first metal layer 120 laminated on one side of the electrostatic layer 110, a second metal layer 130 laminated on the other side of the electrostatic layer 110, a first water retention layer 140 laminated on the side of the first metal layer 120 opposite to the side facing the electrostatic layer 110, and a second water retention layer 150 laminated on the side of the second metal layer 130 opposite to the side facing the electrostatic layer 110.

[0072] The material of the electrostatically charged layer 110 is mainly powdered silicon dioxide, which may be mixed with powdered tuff or the like that has been foamed by heat treatment at a high temperature of about 1000 to 1500° C. as necessary. The power generation efficiency is optimized by mixing silicon dioxide and tuff in a weight ratio of 1 part silicon dioxide to 0.25 to 0.5 parts tuff.

[0073] Furthermore, as a result of the inventor's investigations, it is preferable that the particle size of the powdered silicon dioxide, tuff, etc., that constitutes the charged layer 110 should be limited to approximately 500 μm. In other words, if the particle size of the silicon dioxide, tuff, etc., that constitutes the charged layer 110 is larger than 500 μm, the gaps between adjacent particles become larger, and the amount of negative ions that are charged in the charged layer 110 decreases, which may result in a deterioration in the power generation efficiency of the power generating element 100.

[0074] A first metal layer 120 and a second metal layer 130 are respectively laminated by adhesion on one surface and the other surface of the electrostatic layer 110. In the embodiment of the present invention, the first metal layer 120 is selected as aluminum, which has a higher ionization energy than hydrogen and is easily immersed in water or acid.

[0075] Here, the type of the first metal layer 120 does not necessarily have to be aluminum. As described above, any type of metal may be used as long as it has a higher ionization energy than hydrogen and is easily corroded by water or acid, and may be at least one metal selected from, for example, magnesium, titanium, zinc, chromium, iron, nickel, lead, etc., in addition to aluminum.

[0076] In the embodiment of the present invention, the second metal layer 130 is selected as a metal having an ionization energy lower than that of hydrogen (that is, a metal having a lower ionization tendency than the metal material selected for the first metal layer 120), and is therefore copper.

[0077] Here, the type of the second metal layer 130 does not necessarily have to be copper. As described above, any type of metal may be used as long as it has a lower ionization energy than hydrogen, and for example, in addition to copper, it may be at least one metal selected from gold, silver, copper, platinum, etc.

[0078] First water retention layer 140 and second water retention layer 150 are each made of a paper material capable of absorbing moisture, and because these are materials capable of absorbing moisture from the atmosphere, a certain amount of moisture is always contained in power generation element 100. Then, negative ions generated from first metal layer 120 can be charged to charged layer 110 via the water molecules absorbed by first water retention layer 140 and second water retention layer 150.

[0079] Furthermore, even if the moisture content of the power generating element 100 decreases, since the first moisture retention layer 140 and the second moisture retention layer 150 are adhesively laminated around the power generating element 100, it is easy to supply a specified aqueous solution as needed using a dropper or the like.

[0080] Here, the first water retention layer 140 and the second water retention layer 150 are not necessarily limited to the arrangement described above, and the first water retention layer 140 may be laminated on either side of the first metal layer 120, and the second water retention layer 150 may be laminated on either side of the second metal layer 130.

[0081] As described above, by forming each layer by adhesive lamination, the power generating element 1 having excellent power generating capacity can be easily manufactured. Since the power generating element 100 is larger than the power generating element 1 according to the first embodiment, it can be used as a large-capacity battery such as a battery for an automobile.

[0082] [Example] Next, an example of the power generating element of the present invention will be described. The power generating element used in the example was formed in a thin film by deposition using sputtering, as shown in the power generating element 1 of the first embodiment of the present invention. The first tuff layer 21 and the first silicon dioxide layer 22 were deposited on one surface of the base layer 10 containing a predetermined amount of water (about 2 to 5 drops with a dropper) with a thickness of 20 nm to form the first electrostatic layer 20. The first tuff layer 21 and the first silicon dioxide layer 22 were each deposited to a thickness of 10 nm. The second tuff layer 31 and the second silicon dioxide layer 32 were each deposited on the other surface of the base layer 10 to form the second electrostatic layer 30. The second tuff layer 31 and the second silicon dioxide layer 32 were each deposited to a thickness of 10 nm.

[0083] The first tuff layer 21 and the second tuff layer 31 use powder made by heating and foaming tuff at approximately 1300° C. The silicon dioxide layer consisting of the first silicon dioxide layer 22 and the second silicon dioxide layer 32 is classified into Example 1 (purity 100%), Example 2 (purity 50%), and Comparative Example (purity 20%) according to the purity of the silicon dioxide.

[0084] In addition, a first metal layer 40 made of aluminum is laminated to a thickness of 20 nm on the surface of the first silicon dioxide layer 22 opposite to the surface facing the first tuff layer 21, and a second metal layer 50 made of copper is laminated to a thickness of 20 nm on the surface of the second silicon dioxide layer 32 opposite to the surface facing the second tuff layer 31.

[0085] For the power generating elements 1 according to the above-mentioned Example 1, Example 2, and Comparative Example, a resistor of a predetermined size was connected between the first metal layer 40 and the second metal layer 50 to measure the voltage. Table 1 shows time-series data of the measurement results of the voltage (V) for 20 days from the start of the measurement.

[0086] [Table 1]

[0087] As shown in Table 1, it was confirmed that the higher the purity of the silicon dioxide, the more stable the power generation over the long term. In particular, in Example 1 (silicon dioxide purity 100%), the power generation capacity did not deteriorate significantly even after 20 days had passed since the start of measurement. On the other hand, in the case of the comparative example (silicon dioxide purity less than 20%), the power generation capacity was reduced to about half five days after the start of measurement, confirming the accelerated deterioration of the power generation element. From the above examples and comparative examples, the superiority of the power generation element 1 according to the present invention can be confirmed.

[0088] As described above, the power generating element and the method for manufacturing the power generating element according to the present invention do not require charging with an external voltage, and can increase the power generation efficiency while being small and lightweight. [Explanation of symbols]

[0089] 1, 100 Power generating element 10 Base material layer 20 First electrostatic layer 21 First Tuff Layer 22 First silicon dioxide layer 30 Second electrostatic layer 31 Second Tuff Layer 32 Second silicon dioxide layer 40, 120 1st metal layer 50, 130 second metal layer 60 Insulating layer 110 Charged Layer 140 First Water Retaining Layer 150 Second Water Retention Layer W Conductive Wire T terminal

Claims

1. A substrate layer containing moisture; A first electrostatic layer having a silicon dioxide purity of more than 20% and a first metal layer containing a predetermined type of metal and having a thickness of 20 nm or more are laminated in this order in a lamination direction on one surface of the base material layer; A second electrostatic layer having a silicon dioxide purity of more than 20% and a second metal layer having a thickness of 20 nm or more and containing a predetermined type of metal having a smaller ionization tendency than the metal contained in the first metal layer are laminated in this order in a lamination direction on the other surface of the base layer. Power generating element.

2. The first electrostatic layer is A first tuff layer made of tuff or welded tuff and a first silicon dioxide layer made of silicon dioxide are laminated on one surface of the base layer; The second electrostatic layer is A second tuff layer made of tuff or welded tuff and a second silicon dioxide layer made of silicon dioxide are laminated on the other surface of the base layer. The power generating element according to claim 1 .

3. the first metal layer is made of at least one metal selected from the group consisting of aluminum, titanium, zinc, chromium, iron, nickel, and lead; The second metal layer is made of at least one metal selected from the group consisting of gold, silver, copper, and platinum. The power generating element according to claim 1 or 2.

4. an antistatic layer comprising silicon dioxide; a first metal layer that is laminated on one surface of the charging layer and contains a predetermined type of metal and has a thickness of 20 nm or more; a second metal layer that is laminated on the other surface of the electrostatic layer, contains a predetermined type of metal that has a smaller ionization tendency than the metal contained in the first metal layer, and has a thickness of 20 nm or more; A first water retention layer that is laminated on the first metal layer and contains moisture; A second water retention layer is laminated on the second metal layer and contains moisture. Power generating element.

5. The electrostatic layer is The weight ratio of the silicon dioxide to the tuff or welded tuff is 0.25 to 0.

5. The power generating element according to claim 4 .

6. Providing a substrate layer containing moisture; depositing a first electrostatic layer on one side of the substrate layer, the first electrostatic layer having a silicon dioxide purity of greater than 20%; depositing a second electrostatic layer on the other side of the substrate layer, the second electrostatic layer having a silicon dioxide purity of greater than 20%; a step of depositing a first metal layer containing a predetermined type of metal and having a thickness of 20 nm or more on a surface of the first electrostatic layer opposite to a surface facing the base material layer; and depositing a second metal layer having a thickness of 20 nm or more on a surface of the second electrostatic layer opposite to the surface facing the base material layer, the second metal layer including a predetermined type of metal having a smaller ionization tendency than the metal included in the first metal layer. A method for manufacturing a power generating element.

7. The step of depositing the first electrostatic layer on the substrate layer comprises: The method includes a step of depositing a first tuff layer made of tuff or welded tuff and a first silicon dioxide layer made of silicon dioxide from the base layer in a stacking direction, The step of depositing the second electrostatic layer on the substrate layer comprises: The method includes a step of depositing a second tuff layer made of tuff or welded tuff and a second silicon dioxide layer made of silicon dioxide from the base layer in a stacking direction. The method for producing the power generating element according to claim 6 .

8. forming an antistatic layer comprising silicon dioxide; laminating a first metal layer containing a predetermined type of metal and having a thickness of 20 nm or more on one surface of the charging layer; laminating a second metal layer having a thickness of 20 nm or more on the other surface of the electrostatic layer, the second metal layer including a predetermined type of metal having a smaller ionization tendency than the first metal layer; laminating a first moisture retaining layer capable of absorbing moisture on either a surface of the first metal layer facing the electrostatic layer or a surface opposite to the surface facing the electrostatic layer; and laminating a second moisture retaining layer capable of absorbing moisture on either a surface of the second metal layer facing the electrostatic layer or a surface opposite to the surface facing the electrostatic layer. A method for manufacturing a power generating element.

9. The step of generating an electrostatic layer comprises: Mixing tuff or welded tuff in a weight ratio of 0.25 to 0.5 for every 1 weight ratio of silicon dioxide. The method for producing the power generating element according to claim 8 .

Citation Information

Patent Citations

  • JP171341A

  • Method for manufacturing power generation element using volcanic ash, method for manufacturing battery using volcanic ash, battery using volcanic ash, and battery control device thereof

    JP2005502180A

  • Aqueous activated metal electrochemical cells and systems

    JP2007513464A

  • Polyimide coated separator for lithium battery or capacitor

    JP2022516331A

  • JP272048A